NILAI DIAGNOSTIK MALARIA ANTIGEN CASSETTE PENYAKIT MALARIA - Binawati .; Prihatini .; M.Y Probohoesodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Malaria is an endemic disease in many countries. In 103 endemic countries with around 2.5 billion population, 1−3 million death cases were reported every year. Clinical criteria and blood smear established the diagnosis of malaria. ICT (imuno chromatographytest) is needed in peripheral areas where there are no experienced laboratory technicians. The procedure is simple, practical, easy, aswell as quicker than the conventional method, and no experienced technicians are needed this ICT advantages. The aim of this study isto know the diagnostic value of Malaria Antigen Cassette with microscopic examination as the gold standard examination of malaria.This research used observational cross-sectional method This study was done in Nusa Tenggara Barat during May−June 2008. Bloodsamples were taken by finger prick in patients with Malaria symptoms: fever, chill and sweating, followed by examining the blood smearby Malaria Antigen Cassette from Focus Diagnostic. The diagnostic value was then evaluated by calculating the sensitivity, specificity,positive predictive value as well as the negative predictive value. The diagnostic value of Malaria Antigen Cassette in patients withmalaria falciparum was found as follows: sensitivity 95.2%, specificity 100%, positive predictive value 100%, and negative predictivevalue 97.6%. The diagnostic value of Malaria Antigen Cassette in patients other types than malaria falciparum was as follows: sensitivity94.8%, specificity 100%, positive predictive value 100%, and negative predictive value 95.3%. The diagnostic value of Malaria AntigenCassette was very high in diagnosing malaria falciparum compared to other types than malaria falciparum.